Mali - Public Expenditures Review : Rural Water and Sanitation Sector - World Bank (Washington, DC, 2012)
The review of public expenditure in the sector of potable water and sanitation in rural and semi urban areas aims at supporting the Government of Mali. The review highlighted many sector accomplishments and challenges such as: (i) achieving objectives of the government of passing from 50 percent of access to potable water to 82 percent is difficult but probable; (ii) budget allocations to the sector in real terms increase for more than twice during the last 6 years; (iii) expenditure's increase in the sector has translate into an increase of facilities carried out; (iv) development of the sector is limited by a weak budgetary performance and not by a lack of financing; (v) the weakness of operating budgets hampers the sector's effectiveness; (vi) the traditional systems of facilities management have to be absolutely reconsidered on the basis of lesson learned and the new systems developed with the collaboration of stakeholders; (vii) the sector is well engaged in the approach-program with regard to harmonization and alignment in accordance with the declaration of Paris; (viii) sanitation is neglected. The coverage in family latrines is weak; and (ix) mobilization of resources beyond the state is essential to keep pace with the sector's growth.